2020
DOI: 10.3390/ijerph17103371
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Relationships between Psychological Problems and School Bullying and Non-Suicidal Self-Injury among Rural Primary and Middle School Students in Developing Areas of China

Abstract: (1) Purpose: To analyze the role of psychological problems in connection with school bullying and non-suicidal self-injury (NSSI) among rural primary and middle school students in developing areas of China. (2) Methods: A multi-stage, stratified, cluster random sampling method was used to select 2284 rural primary and middle school students in Jiangxi Province for study. Questionnaires regarding the health risk behaviors of children in developing areas were left behind at primary and middle schools, and they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…There has been a link between the level of psychological distress and the NSSI behaviors (24)(25)(26). According to the emotional cascade model (27), NSSI would be served as a distraction strategy to rapidly reduce an individual's intensive negative feelings, leading to a sense of relief and even increasing their positive feelings.…”
Section: Individual-levelmentioning
confidence: 99%
“…There has been a link between the level of psychological distress and the NSSI behaviors (24)(25)(26). According to the emotional cascade model (27), NSSI would be served as a distraction strategy to rapidly reduce an individual's intensive negative feelings, leading to a sense of relief and even increasing their positive feelings.…”
Section: Individual-levelmentioning
confidence: 99%
“…Regarding indirect effect models of NSSI or SA, only painful feelings can indirectly affect the relationship between campus stressors and NSSI, while painful feelings and pain avoidance can indirectly affect the relationship between campus stressors and SA, which is aligned with our hypothesis. Recent studies also demonstrated the link between stressful events and NSSI in adolescence (Kaess et al, 2020; Li et al, 2020). Considering that the function of NSSI is to relieve negative emotion (Chapman et al, 2006), our results provided support for the emotional regulation theory for NSSI.…”
Section: Discussionmentioning
confidence: 92%
“…However, school bullying was still prevalent among Chinese students. A study showed that 33.36% of primary and secondary school students suffered school bullying in 29 counties in China in 2016 [ 6 ]. In 2019, researchers studying the prevalence of school bullying, its causes, and severity found that 66% of students in Mainland China reported bullying incidents [ 7 ].…”
Section: Introductionmentioning
confidence: 99%